Rebecca of Sunnybrook farm - Wiggin, Kate Douglas Smith, 1856-1923 (Boston, Mass : Thomson Heinle, 2007)
Talkative, ten-year-old Rebecca, goes to live with her spinster aounts, one harsh and demanding, the other soft and sentimental, with whom she spends seven difficult but rewarding years growing up
Title from title screen
Keywords: American literature -- 19th century; Aunts -- Fiction; City and town life -- New Zealand -- Fiction